PERBANDINGAN FLUKS PANAS HASIL OBSERVASI DAN ESTIMASI BULK PARAMETERIZATION - Mukhtar, Kawtsar
In this research,observation have been doing at three different locations in Bandung and surrounding, then heat flux is calculated using the covariance method of vertical windperturbaton and virtual potential temperature perturbation. The result is a diurnal pattern is evident from observations of the heat flux at the three locations with different surfaces. Location observations with urban characteristics have faster heat flux rises, higher when reaching the top and last longer than other locations. Besides the heat flux at night in urban areas is much cooler than elsewhere.Manoko region has the characteristics of the most rapid flux reaching the top and the most rapid decline, while Sulaiman had slowest increase and decrease of a heat flux. Bulk parameterization is one method of estimation that commonly used in weather modelsThe results of the comparison heat flux observation and the estimation, estimation of heat flux has not been able to produce in accordance with observations. Factors atmospheric stability and wind geser alleged bad influence the estimation of flux with bulk parameterization method.